Annals of Bioethics: Regional Perspectives in Bioethics - Cherry, Mark J. (Routledge Annals of Bioethics, 2003)
Regional Perspectives in Bioethics" illustrates the ways in which the national and international political landscape encompasses persons from diverse and often fragmented moral communities with widely varying moral intuitions, premises, evaluations and commitments.